PELATIHAN PERAKITAN KOMPUTER UNTUK MENINGKATKAN PEMAHAMAN PERANGKAT KERAS SISWA KELAS VII SMPN 2 CIMAHI - Tati Ernawati; Muhammad Ahyadi Yusuf; Adhitia Rian Permana; Mamay Syani; Ari Sudrajat; Budi Upayarto (ASOSIASI IDEBAHASA KEPRI, 2026)
Understanding computer hardware is an important skill for the younger generation in facing the technology-based world of work. This PkM activity aims to improve the knowledge and skills of seventh-grade students of SMP Negeri 2 Cimahi in assembling computer components. Based on initial observations, seventh-grade students have not learned about computer assembly, so the team initiated this training program. The implementation method used a practical training and demonstration approach that included material on the function and role of computer hardware such as the motherboard, central processing unit, memory, hard drive, graphics card, power supply unit, system bus, and co-processor, as well as hands-on computer assembly. Evaluation was conducted through question-and-answer sessions and interactive discussions. This training provides a strong foundation for participants in understanding computer hardware and is expected to improve student competence in the field of information and communication technology.